2014
DOI: 10.1177/0306624x14554828
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Level of Program Integrity and Pre- and Post-Test Changes of Responsive–Aggression Regulation Therapy (Re-ART) Outpatient

Abstract: Responsive-Aggression Regulation Therapy (Re-ART) Outpatient is a cognitive behavioral-based intervention for adolescents and young adults (16-24 years) with severe aggressive behavioral problems. This pilot study (N = 26) examined the level of program integrity (PI; that is, the delivery of the intervention as it is originally intended) of Re-ART. We also investigated the pre- and post-test changes in several outcome variables, and the relation between the level of PI and these changes. Participants were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…First, the results show that change might already occur in an early stage of the Re‐ART intervention. Seeing early results might add to the sense of self‐efficacy, or belief in self‐control over one’s actions (55), which may prove fruitful for maintaining motivation and completing the intervention program in a population that is generally reluctant to engage in treatment (25). Second, based on the difference between therapist‐report and adolescent‐report, it is recommended that therapists use multiple sources of information, such as clients and parents, to obtain a better picture of the adolescent’s behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the results show that change might already occur in an early stage of the Re‐ART intervention. Seeing early results might add to the sense of self‐efficacy, or belief in self‐control over one’s actions (55), which may prove fruitful for maintaining motivation and completing the intervention program in a population that is generally reluctant to engage in treatment (25). Second, based on the difference between therapist‐report and adolescent‐report, it is recommended that therapists use multiple sources of information, such as clients and parents, to obtain a better picture of the adolescent’s behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Responsive Aggression Regulation Therapy (Re-ART) is a promising cognitive behavioral intervention that aims to decrease criminal recidivism in delinquent adolescents and young adults with aggressive behavior (24,25). Re-ART has a strong focus on improving EF using modules that target stress reduction, impulse control, anger control, and emotion regulation.…”
mentioning
confidence: 99%
“…Obtaining and maintaining a sufficient level of program integrity is an important part of Re-ART because research shows that the degree of program integrity can affect treatment outcomes (e.g., Arkoosh et al, 2007; Durlak & DuPre, 2008; Goense, Assink, Stams, Boendermaker, & Hoeve, 2016; Hoogsteder, Van Horn, Stams, Wissink, & Hendriks, 2016; Landenberger & Lipsey, 2005). Program integrity refers to the delivery of the intervention as it is intended, including its content, duration, frequency, and scope (Duerden & Witt, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed that Re-ART Residential reduced recidivism as well, with the Re-ART group showing 29.8% less violent recidivism and 37.7% less general recidivism than the control group after 3 years [53]. As of yet, the outpatient version of Re-ART has only been researched in pilot studies, where Re-ART significantly effectuated positive changes in risk of violent recidivism, aggression, coping skills, cognitive distortions, and family functioning [54], and executive functioning [55].…”
Section: Highlightsmentioning
confidence: 99%